PENGARUH KUALITAS PRODUK, SUASANA TOKO DAN MEDIA SOSIAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN DI FORE COFFEE CIBUBUR JUNCTION - Lisna Kurniawati; Parlagutan Silitonga (LPPM Universitas Asa Indonesia, 2021)
The purpose of this research is to determine the effect of qualiy of product, store atmosphere and social media marketing influence on purchase decisions at Fore Coffee Cibubur Junction. The population in this study are customers of Fore Coffee Cibubur Junction. The sample used in this study was 100 respondents by accidental sampling method. The data collection by accidental technique using designed questionaire. The Questionaire has been validated and tested of its reliability, prior to distribution. Data were analyzed by descriptive and quantitative. The regression analysis started with the classical assumption test (normality, multicolinearity, heteroscedasticity and linearity test) afterward by multiple linear regression analysis. The model determined by the hypothesis testing applied F test, t test and correlation test and the coefficient of determination (R2). The results showed that product quality has a significant effect on purchase decisions, store atmosphere has a significant effect on purchase decisions and social media marketing has a significant effect on purchase decisions, while all variables simultaneously showed have a positive results on purchase decision at Fore Coffee Cibubur Junction.